2021
DOI: 10.3389/fpsyg.2021.665658
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Consumer Attention and Arousal Using Eye-Tracking Technology in Virtual Retail Environment

Abstract: This study aims at investigating how consumers experience the retail environment visually, thus establishing a foundation for deeper insights into visual merchandising strategies. Specifically, we experimentally recorded and analyzed the visual attention and emotional arousal of the consumers in a test setting and examined the influence of various elements as well as gender differences in the recorded consumer responses. We conducted an experiment utilizing eye-tracking and virtual reality to analyze visual at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…A follow-up empirical study carrying out a survey (n = 200 or more) could be conducted in order to assess the causal relationships or correlations between the variables influencing users' intentions and actual usage of online secondhand platforms. Beyond self-reporting, future studies could be further developed to assess consumers' retail experience of online secondhand platforms using biometric technology [69,70]. The limited number of participants in the secondhand user survey and the geographic limitations arising from sharing the online survey led to few responses from international users from diverse countries.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up empirical study carrying out a survey (n = 200 or more) could be conducted in order to assess the causal relationships or correlations between the variables influencing users' intentions and actual usage of online secondhand platforms. Beyond self-reporting, future studies could be further developed to assess consumers' retail experience of online secondhand platforms using biometric technology [69,70]. The limited number of participants in the secondhand user survey and the geographic limitations arising from sharing the online survey led to few responses from international users from diverse countries.…”
Section: Discussionmentioning
confidence: 99%
“…Eye-tracking devices used to analyze visual attention and emotional arousal in response to architectural components and interior design elements [28]. In addition, a comparative study could be conducted to distinguish the level of attention of different sectors of groups representing an archetype, with results revealing the characteristics of each group.…”
Section: Biometric Indicators and Interpretationmentioning
confidence: 99%
“…The visual attraction also indicates what design elements should be incorporated for attention. The result of one paper showed that a large media screen in the center of the wall and building with high contrast and punched windows compared to blank or featureless facades induces attention [28].…”
mentioning
confidence: 99%
“…25 In addition to handheld or smartphone pupillometers, virtual reality (VR) and augmented reality (AR) head-mounted displays (HMDs) have begun to incorporate eye-tracking technology with the ability to assess pupil diameter for each eye separately. 26 With these recent advances, we expect to see more applications of VR and AR technology in medicine and may become a useful tool in the future to augment acute teleneurology evaluations. 27,28 Improving Remote Visual Field and Visual Neglect Assessment…”
Section: Pupillary Responsesmentioning
confidence: 99%